Perbaikan Proses Bisnis Pengelolaan Data Penelitian pada Perguruan Tinggi : Sebuah Model Konseptual - MM Wahyuni Inderawati; Ronald Sukwadi; Hotma A. Hutahean (Sanata Dharma University, 2016)
The performance of research and publications was an important measure of the academic reputation in higher education institution. A leading private university in Jakarta had poor performance in research and publications. This research showed that the cause was the lack of good data management mechanism of research and publication. Therefore, it could not give a good report. This research has created a conceptual model of data management research and publications by utilizing information system database. It would produce reports that required by both internal and external stakeholders.